2022
DOI: 10.14366/usg.21011
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasound Liver Imaging Reporting and Data System category M: a systematic review and meta-analysis

Abstract: We performed a meta-analysis to determine the proportion of identifying contrastenhanced ultrasound (CEUS) Liver Imaging Reporting and Data System (LI-RADS) category M (LR-M) in hepatocellular carcinomas (HCCs) and non-HCC malignancies and to determine the frequency of individual CEUS LR-M imaging features. Methods: We searched MEDLINE and EMBASE databases from inception to July 23, 2020, for studies reporting the proportion of CEUS LR-M in HCC and non-HCC malignancies. The meta-analytic pooled proportions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The benefit of these improvement was confirmed in our meta-analysis. Our data aggregation revealed that the proportion of HCC cases in LR-M was 59% according to the ACR algorithm and was similar to the pooled proportion from two meta-analyses, with the proportion of HCC cases in LR-M with SonoVue being 54% ( 30 ) and 57% ( 24 ), which also supports the applicability of the ACR LR-M algorithm for Sonazoid to some extent. However, this proportion was higher in the LR-M modified criteria 1, with HCC accounting for 72.5%, and this proportion reduced to 55.9% in the LR-M modified criteria 2 when the second modification was applied.…”
Section: Discussionsupporting
confidence: 81%
“…The benefit of these improvement was confirmed in our meta-analysis. Our data aggregation revealed that the proportion of HCC cases in LR-M was 59% according to the ACR algorithm and was similar to the pooled proportion from two meta-analyses, with the proportion of HCC cases in LR-M with SonoVue being 54% ( 30 ) and 57% ( 24 ), which also supports the applicability of the ACR LR-M algorithm for Sonazoid to some extent. However, this proportion was higher in the LR-M modified criteria 1, with HCC accounting for 72.5%, and this proportion reduced to 55.9% in the LR-M modified criteria 2 when the second modification was applied.…”
Section: Discussionsupporting
confidence: 81%
“…All LR-M from our cohort were confirmed as malignancies, therefore with better accuracy than that of the CT/MRI LR-M (93%) category reported in a previous meta-analysis [ 27 ]. HCCs represented 44.8% of the LR-M group, while the proportion of other malignancies was 55.1%, which was also higher than in other CEUS LI-RADS studies [ 28 , 29 ], but similar to CT/MRI LI-RADS (57–77%) [ 30 ]. This could be associated with geographic differences in the dominant etiologies of underlying liver disease, which is in accordance with studies from Western countries which had a lower proportion of HCCs and a higher proportion of non-HCC malignancies in the CEUS LR-M category than those from Asian countries [ 29 ].…”
Section: Discussionmentioning
confidence: 67%
“…HCCs represented 44.8% of the LR-M group, while the proportion of other malignancies was 55.1%, which was also higher than in other CEUS LI-RADS studies [ 28 , 29 ], but similar to CT/MRI LI-RADS (57–77%) [ 30 ]. This could be associated with geographic differences in the dominant etiologies of underlying liver disease, which is in accordance with studies from Western countries which had a lower proportion of HCCs and a higher proportion of non-HCC malignancies in the CEUS LR-M category than those from Asian countries [ 29 ]. Furthermore, in our cohort, 48.2% of non-HCC malignant nodules had suggestive early washout <60 s. In a recent meta-analysis, the majority of all CEUS LR-M lesions were malignancies (94%), with HCCs representing 54% and non-HCC malignancies representing 40%.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation